Factors associated with nursing workload in three intensive care units (2021)
Objective: To determine the nursing workload in intensive care units (ICUs) and the factors associated with the Nursing Activities Score (NAS). Method: An analytical cross-sectional study was carried out in three ICUs in Bucaramanga, Colombia, between February 2018 and February 2020. The nursing workload was estimated based on the NAS. A descriptive and bivariate analysis stratified by ICU was performed using a robust multiple linear regression model, and the factors associated with the nursing workload (p < 0.05) were estimated. Results: In this study, 362 records were included. The median NAS was 68.1 points (Q1:47.2–Q3:116.7). APACHE II (β = 3.13, CI: 95% 2.28; 3.98), days of stay in ICU ≥3 (β = 16.78, CI: 95% 6.15; 27.41), surgery provenance service (β = 22.31, CI: 95% 9.76; 34.86), and traumatology and emergencies diagnostic category (β = 33.72, CI 95%: 9.90; 57.53) were associated with high NAS scores. Conclusion: The nursing staff spend approximately 70% of their time on a single patient, and administrative work takes up most of their time. Hospital stays of longer than 3 days, high APACHE II score, coming from the surgery department, and having a diagnosis of trauma and emergency were associated with a high workload.